Experimental Investigation of the Influence of Sand and Binder Composition on the Mold Properties of Alkyd Type No-Bake Chemically Bonded Sand-Casting System - Keerthana, J. (Asian Review of Mechanical Engineering, 2022)
In comparison to green sand moulds, chemically bonded resin sand moulds have better dimensional accuracy, surface quality, and sand mould qualities. To survive sand drops when pouring molten metal, the mould cavity formed using a chemically bonded sand mould technique must have appropriate permeability, strength, and hardness. The desire for better permeability, strength, and mould hardness is based on a thorough investigation and analysis of the affecting parameters, such as resin percentage, hardener, and catalyst. The influence of binder content on the moulding qualities of silica sand bound with Alkyd oil urethane binder was investigated. Using a sieve shaker, the experimental materials were sieved and manually blended with the binders. AFS standard test specimens (50 mm diameter by 50 mm height) were prepared using a sand rammer, and four key moulding parameters were determined using a universal sand strength machine, permeability meter, and mould hardness tester: green compression strength (GCS), green shear strength (GSS), permeability, and mould hardness. For the minimal experiments, Box-Behnken experimental matrices were used, and the statistical significance of influencing factors and their interactions will be identified to manage the process. To statistically validate the model, an analysis of variance (ANOVA) test was performed using Minitab. Mold hardness, strength, and permeability will each have their own mathematical equation, which was stated as a nonlinear function of input factors based on experimental input-output data. To optimize the process parameters, a response optimizer (using Minitab) has been used. The results revealed that increasing the resin concentration from 1% to 2% enhances permeability and GSS while decreasing GCS and mould hardness. Hardener was increased from 18 to 20%, which resulted in a drop in permeability and GSS but an increase in GCS and mould hardness. Similarly, increasing the catalyst concentration from 2% to 10% reduces permeability and mould hardness while increasing GCS and GSS.